Evaluation of impedance spectroscopy as a tool to characterize degradation mechanisms in silicon photovoltaics. (15th May 2019) - Yeow, Travis; Sun, Jing; Yao, Zheng; Jaubert, Jean-Nicolas; Musselman, Kevin P.
Highlights: PERC cells and modules with PID and CID were analyzed by impedance spectroscopy. Bifacial modules with PID showed a reduced shunt resistance and some inhomogeneity. Characterization of CID in modules was not possible with a standard spectrometer. Carrier lifetimes measured in PERC cells with CID correlate with the PCE. A current-induced regeneration process was found to reduce CID in the PERC cells. Abstract: Advancements in photovoltaic technologies are hindered by degradation mechanisms such as potential induced degradation (PID) and current-induced degradation (CID). In this work, impedance spectroscopy is used to examine passivated emitter and rear cell (PERC) silicon modules with PID and CID. A comparison between control and degraded modules is done to identify key differences in the impedance spectra and determine the extent of the degradation. PID was observed at the module level as a dramatic reduction in shunt resistance, with a small amount of spatial inhomogeneity present in the degradation. It was found that accurate characterization of CID via measurement of the minority carrier lifetime requires a high bias voltage at the module level that exceeds the capabilities of a standard impedance spectrometer. Because of this, CID was also examined at the cell level, where reductions in minority carrier lifetimes could be accurately measured. A correlation between the reduction in minority carrier lifetime due to CID and a reduction in the power conversion efficiency was observed. Thus the PID and CID mechanisms studied here induce unique changes in the impedance spectroscopy results, making them distinguishable and quantifiable. Finally, the ability to mitigate CID through the use of different silicon wafers and a current induced regeneration process was characterized by impedance spectroscopy.